Beam, slab and shear wall construction / Muhammad Abdillah Mohamad Nor - Mohamad Nor, Muhammad Abdillah (Universiti Teknologi MARA, Perak, 2019)
Construction is one of the never-ending developing industries. Around the world. Contractors are racing to provide the best quality and method for a construction project. This report discussed the construction method of Beam, Slab and Shear Wall. It is conducted in a construction site at Klebang, Melaka. The objective is to study the construction method for beam, slab and shear wall. It is mainly focused on how the construction is managed from the early stages until it is finished, including the precaution steps taken during construction. Progress of the construction is inspected daily, to find out the details of the construction. Several workers are interviewed for deeper understanding on how the construction methods are taken. The method used during construction work is important as it defines the efficiency of the working progress of a construction.